1996
DOI: 10.1097/00005537-199602000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Labyrinthectomy and Vestibular Neurectomy in the Control of Vertigo

Abstract: One hundred twenty-six patients who were treated with labyrinthectomy (81 patients) or vestibular neurectomy (45) between the years 1979 and 1994 were reviewed. The cause for vertigo in 124 of the 126 patients was Meniere's disease (89 patients), labyrinthitis (15), delayed endolymphatic hydrops (8), vestibular neuritis (7), and failed labyrinthectomy (5). In the remaining 2 patients, a normal labyrinth was sacrificed to fistulize a petrous apex cyst. Both procedures were equally effective in relieving vertigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 15 publications
3
22
0
Order By: Relevance
“…Vestibular imbalance should be compensated more rapidly when the vestibular nerve and scarpa's ganglion are preserved. This phenomenon has also been reported in previous animal studies that have proven that the recovery of imbalance was faster when the vestibular ganglion was preserved (11,12,14).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Vestibular imbalance should be compensated more rapidly when the vestibular nerve and scarpa's ganglion are preserved. This phenomenon has also been reported in previous animal studies that have proven that the recovery of imbalance was faster when the vestibular ganglion was preserved (11,12,14).…”
Section: Discussionsupporting
confidence: 86%
“…In this regard, some authors have argued that VN is similar to the postoperative status of vestibular neurectony, whereas SHLV is more similar to the postoperative status of labyrinthectomy (10). After labyrinthectomy, patients have been reported to be less annoyed by postoperative motion evoked dizziness than patients are after vestibular neurectomy (11,12). Similarly, it has been reported that the time to compensate for vestibular imbalance is longer in those with VN when compared to those with SHLV (10).…”
mentioning
confidence: 99%
“…In our experience 30% of MD patients may have improvement in hearing following antiviral therapy. Such an improvement in hearing has been reported following middle fossa excision of the vestibular ganglion, which represents removal of virus-containing neurons [22]. …”
Section: Pathology Of Vn MD and Bppvmentioning
confidence: 77%
“…Nevertheless, on this basis repositioning of the loose otoconia by physical maneuvers has gained popular support as conservative management of symptoms. As well the conservative measures used to relieve vertigo in MD [19] and BPPV [20,21,22] have yielded equivocal results when evaluated in controlled studies. Only ablation of the responsible sense organ has yielded a significant level of relief [15,23].…”
Section: Definitionsmentioning
confidence: 99%
“…However, transmastoid labyrinthectomy and a translabyrinthine vestibular nerve section were shown to offer the same benefit in the control of intractable episodic vertigo [29]. It was also suggested that longterm clinical balance and hearing outcomes of transmastoid labyrinthectomy and retrosigmoid vestibular neurectomy are equivalent with a vertigo control rate exceeding 90% [30,31]. This contention can be considered true when labyrinthectomy is performed completely without leaving a residual vestibular tissue.…”
Section: Labyrinthectomymentioning
confidence: 99%